Paradise Trashed: Sources and solutions to marine litter in a small island developing state. (15th February 2020) - Verlis, Krista M.; Wilson, Scott P.
Graphical abstract: Highlights: Marine litter loads on French Polynesian beaches were classed as 'dirty'. The majority of littered items originated from local land-based sources. Some local abatement measures have shown to be effective. Improved waste management infrastructure is still needed. Abstract: Anthropogenic marine litter pollution is a serious issue facing oceans worldwide. Limited data exists on this pollution issue for South Pacific Island nations and for Small Island Developing States (SIDS) in general. This study presents the first extensive baseline survey of macro-sized marine litter on Mo'orea (0.75 items m −2 ) and Tahiti (0.95 items m −2 ), French Polynesia. Not unexpectedly, marine litter was dominated by plastics (58%); however, glass also made up a significant portion (21%). Sixty percent of recovered marine litter from both islands was derived from local land-based catchments, indicating that the bulk of the litter is from local sources. Measures to address the waste issue in French Polynesia will be discussed with a cash-for-container scheme for locally produced beer showing promising positive environmental results, and further strategies for waste management in SIDS raised.